Хижняков В. Чернігівська старовина - Демченко, Т.; Шара, Л. (Сiверянський лiтопис, 2017)
Рецензія на книгу: Хижняков В. Чернігівська старовина / підгот. до друку і вступ. ст.
О. Б. Коваленка, А. Л. Курданова, О. Я. Рахна. – Чернігів: Десна Поліграф, 2016. – 352 с.